Altruism : it's importance in sustaining microfinance development / Siti Khadijah Ab Manan, Mohd. Faizal Kamarudin and Nor Effuandy Pfordten Mohd. Saleh - Ab Manan, Siti Khadijah; Kamarudin, Mohd. Faizal; Mohd. Saleh, Nor Effuandy Pfordten (Academy of Contemporary Islamic Studies, 2015)
Sustaining microfinance institutions is important in ensuring that the sources of capital of the smaller and micro enterprises could be maintained. This paper examined the important role of altruism in sustaining the progress and development of microfinance institutions. Using qualitative method of study, this article presents the relative importance of altruism in facilitating the development of Islamic microfinance. The practice of IMF in Malaysia and Indonesia was discussed comparatively to give an outlook on the importance of altruism in ensuring the sustainability of microfinance institutions. The study indicated that being aware and understanding this would help the policy makers and practitioners in designing fundraising strategies for this inherently less popular project.